Pengaruh Pemberian Jahe terhadap Penurunan Mual Muntah pada Ibu Hamil Trimester I - Dina Novitasari; Enny Yuliaswati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Background: Pregnancy is the implantation of the fertilized egg and sperm in the endometrium, and can cause discomfort, one of which is nausea and vomiting, especially in the first trimester. This symptom is common and can cause decreased appetite, paleness, weakness and decreased body fluids. The prevalence of nausea and vomiting in Indonesia is 50-90% of pregnant women. This condition occurs in 60-80% of primigravida pregnant women, and 40-60% of multigravida pregnant women. Objective: This study aims to determine the effect of ginger administration on reducing nausea and vomiting in pregnant women in the first trimester. Method: The method used is a pre-experimental method with a one-group pretest-posttest approach. The sample consisted of 22 respondents who experienced nausea and vomiting at the Simo Community Health Center, Boyolali. The sampling technique used a non-probability method with a consecutive sampling technique. Data analysis used the Wilcoxon Signed Rank test. Assessment of nausea and vomiting using the Pregnancy Unique Quantification of Emesis (PUQE-24) before and after administration of ginger for 4 days. Results: The majority of respondents before the intervention experienced moderate nausea and vomiting (54.5%), while after the intervention, the majority experienced mild nausea and vomiting (59.1%), and those who did not experience nausea and vomiting (31.8%). The Wilcoxon signed rank test showed that nausea and vomiting before and after ginger administration resulted in a p value of 0.000 (<0.05). Conclusion: Ginger administration has a significant and effective effect on reducing the level of nausea and vomiting in pregnant women in the first trimester.